Identity negotiation and cross-cultural strategies of Young Southeast Asian Leaders Initiative participants - Yozani, Ringgo Eldapi; Arifin, Mohd Yahya Mohammed; Octavianti, Meria; Sari, Genny Gustina; Handoko, Tito; Azzmi, Muhammad (Faculty of Communication Sciences Universitas Padjadjaran, 2026)
Background: Existing research on face negotiation tends to overlook short-term leadership exchange programs, resulting in a limited understanding of how participants navigate the contrasting communication styles between Southeast Asian high-context cultures and the low-context culture of the United States. Purpose: This study aims to examine the intercultural communication strategies and identity negotiation practices of participants in the Young Southeast Asian Leaders Initiative (YSEALI) 2022–2025 cohort during their exchange in the United States, with a particular focus on how they manage self-face, other-face, and mutual-face concerns. Methods: Employing a qualitative descriptive approach, data were collected through in-depth interviews with 11 participants representing 11 Southeast Asian countries and analyzed using Stella Ting-Toomey’s Face Negotiation Theory. Results: The findings indicate that self-face was primarily expressed through symbolic cultural representations rather than direct verbal confrontation, whereas other-face concerns were managed by avoiding sensitive topics to preserve interpersonal harmony. Mutual-face was achieved through inclusive and collaborative communication styles that emphasized group cohesion and shared understanding. Conclusion: The study concludes that Face Negotiation Theory provides a valuable framework for understanding how individuals from collectivist cultures adapt in short-term intercultural exchanges, demonstrating that cultural identity can serve as a bridge rather than a barrier to effective communication. Implications: These findings have important implications for advancing efforts to reduce social inequalities, suggesting that program organizers should implement targeted pre-departure orientations focusing on intercultural communication styles to enhance participants’ adaptability and foster more inclusive interactions.